2005
DOI: 10.1111/j.1440-1681.2005.04235.x
|View full text |Cite
|
Sign up to set email alerts
|

WAGNER‐NELSON METHOD FOR ANALYSING THE ATYPICAL DOUBLE‐PEAKED [13CO2] EXCRETION CURVE IN THE [13C]‐OCTANOATE GASTRIC EMPTYING BREATH TEST IN HUMANS

Abstract: 1. In the [(13)C]-octanoic acid breath test, the time versus pulmonary [(13)CO(2)] excretion rate curve is analysed using mathematical curve-fitting techniques to calculate gastric emptying parameters. Thus, the goodness-of-fit highly influences the accuracy of the breath test. However, a double-peaked [(13)CO(2)] excretion curve, which occasionally develops owing to the presence of an interval of quiescent gastric emptying (the plateau phase), is likely to be fitted poorly. 2. In pharmacokinetics, the Wagner-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Various mathematical models (e.g. Wagner Nelson method) try to make the 13 C-breath test kinetics comparable to radioscintigraphy curves and adjust for the passage of the 13 C-tracer through the metabolic pathways and for the fixation and loss in the bicarbonate pool [56]. In the author's opinion we should be aware of the differences in the methods but should not adjust for factors we do not measure in order to get similar curves to scintigraphy.…”
Section: Analysis and Interpretation Of 13 C-breath Tests In Gastric mentioning
confidence: 98%
“…Various mathematical models (e.g. Wagner Nelson method) try to make the 13 C-breath test kinetics comparable to radioscintigraphy curves and adjust for the passage of the 13 C-tracer through the metabolic pathways and for the fixation and loss in the bicarbonate pool [56]. In the author's opinion we should be aware of the differences in the methods but should not adjust for factors we do not measure in order to get similar curves to scintigraphy.…”
Section: Analysis and Interpretation Of 13 C-breath Tests In Gastric mentioning
confidence: 98%
“…Its relevance has recently been validated against the sonographic measurement of liquid GE (6). More recently, it has been suggested that Wagner-Nelson analysis is versatile enough to decipher atypical GE patterns (4). To verify the versatility, we show here that a GE curve prepared by the Wagner-Nelson method can accurately reproduce atypical behavior of GE that is experimentally induced.…”
Section: To Precisely Describe a Profile Of Bizarre Gastric Emptying mentioning
confidence: 82%
“…A breath (t) to each time point was calculated manually according to the trapezoidal rule, and C(t)/0.65 at the corresponding time was then added to each AUC(t). A breath (∞) was computed as A breath (4.0) + C(4.0)/0.65 (4,6). A breath (t) and A breath (t) + C(t)/0.65 were divided by A breath (∞).…”
Section: To Precisely Describe a Profile Of Bizarre Gastric Emptying mentioning
confidence: 99%
“…Ritz et al [24] observed a delayed emptying for ICU patients. In 7 out of 30 cases the 13 CO 2 profile either showed bi-phasic peaks or irregular patterns, which implies profound distortions in gastric motility and has to be handled with more elaborate evaluation schemes [25]. Chiolero et al [26], however, reported that the delay of 13 CO 2 release due to absorption and metabolism does not assume major importance in the critically ill patient.…”
Section: Gastric Emptyingmentioning
confidence: 98%